2015
DOI: 10.1007/s11414-015-9490-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Business Case for Telemental Health in Rural Communities

Abstract: Telemental health has been promoted to address long-standing access barriers to rural mental health care, including low supply and long travel distances. Examples of rural telemental health programs are common; there is a less clear picture of how widely implemented these programs are, their organization, staffing, and services. There is also a need to understand the business case for these programs and assess whether and how they might realize their promise. To address these gaps, a national study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…While large integrated health care systems such as the Veterans Health Administration have been able to successfully deploy TMH at scale, small independent rural primary care practices have lagged behind. Even when TMH programs are successfully launched with grant funding, they often fail to transition to financial sustainability . In this paper, we share our experience launching the Study to Promote Innovation in Rural Integrated Telepsychiatry (SPIRIT) trial, a large pragmatic trial (PCS‐1406‐19295) comparing 2 approaches to TMH in Federally Qualified Health Centers (FQHCs) serving rural areas of Arkansas, Michigan, and Washington state.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While large integrated health care systems such as the Veterans Health Administration have been able to successfully deploy TMH at scale, small independent rural primary care practices have lagged behind. Even when TMH programs are successfully launched with grant funding, they often fail to transition to financial sustainability . In this paper, we share our experience launching the Study to Promote Innovation in Rural Integrated Telepsychiatry (SPIRIT) trial, a large pragmatic trial (PCS‐1406‐19295) comparing 2 approaches to TMH in Federally Qualified Health Centers (FQHCs) serving rural areas of Arkansas, Michigan, and Washington state.…”
mentioning
confidence: 99%
“…Even when TMH programs are successfully launched with grant funding, they often fail to transition to financial sustainability. 17 In this paper, we share our experience launching the Study to Promote Innovation in Rural Integrated Telepsychiatry (SPIRIT) trial, a large pragmatic trial (PCS-1406-19295) comparing 2 approaches to TMH in Federally Qualified Health Centers (FQHCs) serving rural areas of Arkansas, Michigan, and Washington state. Supported by the Health Services and Resources Administration (HRSA), FQHCs deliver primary care services in areas where geographic, economic, and/or cultural barriers limit access to care.…”
mentioning
confidence: 99%
“…Technology was expensive, and the equipment was enormous, often housed at academic medical centers or larger medical institutions. Visual/audio technology was less sophisticated, and not many sites offered telehealth as a treatment modality (Lambert et al, 2016).…”
Section: Historical Development Of the Theorymentioning
confidence: 99%
“…These trends are echoed in a recent study revealing that respondents living in rural areas were less likely to use telehealth than their urban counterparts (Jaffe et al, 2020 ). Many scholars concluded that the key reasons for low utilization rates of telemedicine among rural populations can mainly be explained by the shortage of mental health specialists offering this service, the absence of coverage and reimbursement, licensure issues, broadband access and adequacy, access to appropriate technology, and privacy and security concerns (Fortney et al, 2015 ; Goins et al, 2001 ; Lambert et al, 2016 ; Mehrotra et al, 2017 ; Myers, 2019 ; Park et al, 2018 ; Patient Engagement HIT, 2020 ).…”
Section: Introductionmentioning
confidence: 99%